Reliability and validity of the Turkish Version of Arthritis Research UK Musculoskeletal Health Questionnaire - Yasemin AKKUBAK; Bahar ANAFOROĞLU KÜLÜNKOĞLU (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the validity and reliability of the Turkish version of the Musculoskeletal Health Questionnaire (MSK-HQ-T) for assessing the general health status in patients with axial spondyloarthritis (ax-SpA). Materials and methods: One hundred ax-SpA patients (42 males, 58 females; mean age 40.3±9.1 years; range, 18 to 65 years) who were able to speak and understand Turkish language were included in this study. All participants answered MSK-HQ-T, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI) and Short-Form 36 (SF-36). MSK-HQ-T was repeated five-seven days later for test-retest and internal consistency reliability. Results: The Cronbach’s alpha value was 0.912, demonstrating high internal consistency. The test-retest score of MSK-HQ-T was 0.968, which was significant. The correlation of MSK-HQ-T with the subgroup scores of SF-36 was statistically significant (p<0.001). The correlation between MSK-HQ-T and the total scores of BASDAI and BASFI was statistically significant (r=-0.788, p<0.001; r=-0.743, p<0.001). Conclusion: The MSK-HQ-T is a reliable and valid questionnaire to assess general health status in Turkish patients with ax-SpA.